Identification and analysis of pathologies in bridges of urban and rural roads - Tadeu Mascia, Nilson; Lenz Sartorti, Artur (Revista Ingeniería de Construcción, 2011)
A concern with a great number of bridges with significant pathological problems was the motivating factor to carry out this research. Small and medium size bridges have significant relevance for the economic and social development of the country, because they must ensure the transit of people, vehicles with raw material and local produce. However, the precarious conditions of bridges in the urban and rural areas make the displacement difficult, causing discomfort and unsafety for users. Furthermore, the transportation costs for producers and the maintenance for the local government continue to increase. This article intends to show the conservation conditions of small and medium sized bridges in the urban and rural region of Campinas (SP)-Brazil. Thus, this study is based on the analysis of four bridges of this region, in which is presented several examples in situ of the pathological manifestations in concrete, steel and wood bridges. This article also focuses on the design of bridges and its relationship with the pathological condition establishing concepts that could be applied to the corrective method and the pathology identification in concrete, steel and wood bridges. Finally, it aims to conclude that the most appropriate way to avoid a pathological state is preventive maintenance.